2015
DOI: 10.1155/2015/328796
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Antibiotic Susceptibility of the Microorganisms Isolated from Diabetic Foot Infections in Nemazee Hospital, Southern Iran

Abstract: Background. Diabetic foot infections (DFIs) are a major public health issue and identification of the microorganisms causing such polymicrobial infections is useful to find out appropriate antibiotic therapy. Meanwhile, many reports have shown antibiotic resistance rising dramatically. In the present study, we sought to determine the prevalence of microorganisms detected on culture in complicated DFIs in hospitalized patients and their antibiotic sensitivity profiles. Methods. A cross-sectional study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
47
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 38 publications
(32 reference statements)
18
47
5
1
Order By: Relevance
“…Antibiotic resistance is another factor considered for repeated colonization (13), and it is mandatory for every hospital or clinical setting to perform an accurate detection of MRSA. Knowledge of the prevalence of antibiotic resistance is a pre-requisite for infection control, and national guidelines for treatment are essential for the policy makers of public healthcare to conduct effective responses (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance is another factor considered for repeated colonization (13), and it is mandatory for every hospital or clinical setting to perform an accurate detection of MRSA. Knowledge of the prevalence of antibiotic resistance is a pre-requisite for infection control, and national guidelines for treatment are essential for the policy makers of public healthcare to conduct effective responses (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that though there was a decrease in antimicrobial prescribing for these two conditions but there was enormous increase in prescribing of broad spectrum antimicrobials (i.e. from 10.6% to 40.5%) 14 . The emerging problem of antibiotic resistance has become a major threat to the medical field.…”
Section: Disease Of the Nose: Sinus Infectionmentioning
confidence: 99%
“…The VRE isolates include two E. faecalis and the one E. faecium were isolated and resistant to eight tested antibiotics (Olawale et al, 2011).The high prevalence of Enterococci has developed as a public health threat. Anvarinejad et al, (2015) indicated that the Enterococci are the most common bacteria present in immune-compromised patients, such as diabetics, and in their foot ulcers, but their part in corruptions at these sites is not clearly detected.…”
Section: History Of Enterococcus Feacalis Diseasesmentioning
confidence: 99%
“…were frequently isolated from 34 (39.5%) patients consisting of 20 males (59%) and 14 females (41%), and showed a high degree of resistance to vancomycin. Knowing of the causative microbes in Diabetic Foot Infections (DFIs) and their antibiotic susceptibility profiles is an important step for an appropriate treatment and eradication of infection (Anvarinejad et al, 2015). In Portugal all Enterococcus species isolated from diabetic foot infections were considered as resistant to different antibacterial agents, gelatinase and cytolysin creators, and the majority also established the aptitude to harvest biofilms these consequences show the importance of enterococci in diabetic foot infection advance and persistence, particularly concerning their biofilm forming aptitude and resistance to clinically pertinent antibiotics (SemedoLemsaddek et al, 2016).…”
Section: Diabetic Foot Infectionsmentioning
confidence: 99%